2017
DOI: 10.1371/journal.pone.0170649
|View full text |Cite
|
Sign up to set email alerts
|

The Iron-Dependent Regulation of the Candida albicans Oxidative Stress Response by the CCAAT-Binding Factor

Abstract: Candida albicans is the most frequently encountered fungal pathogen in humans, capable of causing mucocutaneous and systemic infections in immunocompromised individuals. C. albicans virulence is influenced by multiple factors. Importantly, iron acquisition and avoidance of the immune oxidative burst are two critical barriers for survival in the host. Prior studies using whole genome microarray expression data indicated that the CCAAT-binding factor is involved in the regulation of iron uptake/utilization and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 69 publications
3
15
0
Order By: Relevance
“…A characteristic histone fold domain (HFD) is commonly recognized as the structural marker for all Hap3 homologs, and structurally, this motif is composed of a long central α-helix flanked by two smaller α-helices and is dimerized through the extensive hydrophobic contact in a head-to-tail assembly mode (Arents et al, 1991; Gnesutta et al, 2013; Hortschansky et al, 2017). The C. albicans Hap3 contains two distinct homologs, namely Hap31 and Hap32, and studies have shown that Hap31 and Hap32 individually interact with Hap2 and Hap5 to form DNA-binding complexes under different iron conditions (Singh et al, 2011; Chakravarti et al, 2017).…”
Section: Architecture Of the Hap Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…A characteristic histone fold domain (HFD) is commonly recognized as the structural marker for all Hap3 homologs, and structurally, this motif is composed of a long central α-helix flanked by two smaller α-helices and is dimerized through the extensive hydrophobic contact in a head-to-tail assembly mode (Arents et al, 1991; Gnesutta et al, 2013; Hortschansky et al, 2017). The C. albicans Hap3 contains two distinct homologs, namely Hap31 and Hap32, and studies have shown that Hap31 and Hap32 individually interact with Hap2 and Hap5 to form DNA-binding complexes under different iron conditions (Singh et al, 2011; Chakravarti et al, 2017).…”
Section: Architecture Of the Hap Complexmentioning
confidence: 99%
“…Studies have shown that the Hap complex is one of the major redox sensors for yeast cells and a member of the fine-tuning mechanism that adapts to different levels of oxidative stress (Thön et al, 2007; Chevtzoff et al, 2010; Marinho et al, 2014). For example, the subunits Hap2, Hap31/32, and Hap5 in C. albicans were found to be actively involved in regulating the expression of oxidative stress genes (e.g., CAT1 , SOD4 , GRX5 , and TRX1 ) in response to iron availability (Chakravarti et al, 2017).…”
Section: Gene Regulation Of Hap Complex In Yeastsmentioning
confidence: 99%
“…4D). Taken together, removal of GCN5 differentially regulates genes involved in oxido-reduction, ABC and MFS drug transporters, filamentation regulators, MAPK signaling modules, as well as iron / zinc homeostasis and heme acquisition, which requires Rbt5 and affects cell wall architecture by regulating its proteome including adhesins 7074 .…”
Section: Resultsmentioning
confidence: 99%
“…glabrata 96 . Interestingly, iron homeostasis is tightly linked to cell wall architecture, and Gcn5 regulates expression of Rbt5 that affects cell wall architecture by regulating adhesins and the entire surface proteome 7074 . In addition, Gcn5 selectively controls hyphal regulator genes such as EFG1 , TEC1 , but also hyphal genes, including HWP1 and ECE1 .…”
Section: Discussionmentioning
confidence: 99%
“…Hap43 in turn represses iron consuming processes and induces iron uptake genes (Baek et al, 2008 ; Singh et al, 2011 ). Interestingly, the CCAAT-binding factor also plays a role in the regulation of the oxidative stress response in C. albicans (Chakravarti et al, 2017 ). In addition to this, Hap43 represses the GATA family transcription factor Sfu1.…”
Section: Regulation Of Iron Acquisition In Candida Albicansmentioning
confidence: 99%